Evaluation of Forensic Psychiatric Report for Sexual Assault Cases - Şenol, Ender; Meral, Orhan; Sertöz, Özen Önen; Altıntoprak, Ayşe Ender; Coşkunol, Hakan; Güler, Hülya (The Bulletin of Legal Medicine, 2016)
Objective: Sex crimes remain a social concern affecting people of all ages globally. It is known that sex crimes pave the way for many mental disturbances. In this study, it was aimed to investigate the demographics of sexual assault victims, features of sexual assaults and the results of the reports evaluated by Ege University Faculty of Medicine Adult Judicial Council and to compare those to other studies in literature.Materials and Methods: Records of cases sent with their files for report preparation to Ege University, Faculty of Medicine, Department of Psychiatry, Judicial Council between 2012 - 2014 were examined retrospectively and the data were evaluated with SPSS 18 for Windows.Results: 12 (%3.9) of 311 cases which were reported between 01.01.2012-31.12.2014 were male and 299 (%96.1) were female. Ages at the time of the event ranged between 6 and 89 and the aver- age was 26.58+12.22 %37 (n=115) of the reports were requested by High Criminal Courts. %56.9 (n=177) of the sexual assaults claimed to occur were qualified/aggravated, %80.7 (n=251) of the victims’ presses charges themselves, all of the offenders were male, %70.1 (n=218) of the offenders were people from the neighbor- hood of the victim. As a result of the event, %61,4 (n=191) of the victims developed one, %34.1 (n=106) developed more than one psychiatric disorders.Conclusion: Mental disorders sexual assault victims are diagnosed with and the fact that sexual assaults are performed by mostly men against women and children of all ages were consistent with the literature.
Keywords: sexual assault; sexual abuse; mental health deterioration; judicial report